Parallel Processing Models For Image Processing Problems - Salleh, Shaharuddin; Sanugi, Bahrom (Universiti Teknologi Malaysia, 2002)
This report is the compilation of our research work under IRPA Vot no. 72179. The work consists of four main problems of study. First, we look at the stochastic task scheduling problem using the reconfigurable mesh network as the computing platform. Through our model called the Dynamic Simulator on Reconfigurable Mesh (DSRM) which maps a randomly generated number of tasks onto the processors at discrete time, some reasonably good load balancing results were obtained. The second problem is the application of the first model in the edge detection problem using the Laplacian convolution method on the same parallel computing network. In the third problem, we extend the scope to include a strategy for the single-row routing of pins and vias in VLSI design, using our model called the Enhanced Simulated annealing for Single-row Routing (ESSR). This model is the parallel implementation of the simulated annealing method, and it generates optimum solutions to the problem. The fourth problem is the extension of the single-row routing problem, where a model has been developed to transform a complete graph into its single-row representation. This last problem has some significant contributions in applications such as scheduling and channel assignment problem in cellular telephone systems.